2009
DOI: 10.1038/emboj.2009.47
|View full text |Cite
|
Sign up to set email alerts
|

Microtubule nucleation at the cis-side of the Golgi apparatus requires AKAP450 and GM130

Abstract: We report that microtubule (MT) nucleation at the Golgi apparatus requires AKAP450, a centrosomal c-TuRC-interacting protein that also forms a distinct network associated with the Golgi. Depletion of AKAP450 abolished MT nucleation at the Golgi, whereas depletion of the cis-Golgi protein GM130 led to the disorganisation of AKAP450 network and impairment of MT nucleation. Brefeldin-A treatment induced relocalisation of AKAP450 to ER exit sites and concomitant redistribution of MT nucleation capacity to the ER. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

29
390
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 288 publications
(422 citation statements)
references
References 36 publications
29
390
1
Order By: Relevance
“…7). These results indicate that MTCL1 plays essential roles in the stable growing of MTs from the Golgi membrane, as has been demonstrated for CLASPs and AKAP450/ CG-NAP 8,9 .…”
mentioning
confidence: 48%
See 3 more Smart Citations
“…7). These results indicate that MTCL1 plays essential roles in the stable growing of MTs from the Golgi membrane, as has been demonstrated for CLASPs and AKAP450/ CG-NAP 8,9 .…”
mentioning
confidence: 48%
“…However, the underlying mechanism for maintaining this specific Golgi arrangement as well as its physiological significance had been unclear until the above-mentioned studies. They have demonstrated that specific disruption of the Golgi-derived MTs by knockdown of CLASPs or AKAP450/CG-NAP converted the Golgi ribbon into a cluster of Golgi stacks gathering around the centrosome 7,9 . Together with data from live imaging analyses 7 , these results have indicated that the formation of the Golgi ribbon proceeds in two distinct steps, in which the Golgi-derived MTs first draw the Golgi ministacks together in a tangential manner, whereas the centrosomal MTs subsequently drag the laterally clustered Golgi stacks towards the centrosome 7 .…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…57 In addition to this outpost fusion function, GM130 may also recruit AKAP450/Plp to outposts, as it has been shown to link AKAP450/Plp to somatic Golgi for microtubule nucleation. 58 The role of alternative nucleation sites in orienting microtubule nucleation in the dendrite…”
Section: Microtubule Nucleation At Golgi Outpostsmentioning
confidence: 99%